simplify:(5+root11)(5-root11)
Answers
Answered by
17
Hey friend, ☺ here is ur answer ___________________________
![(5 + \sqrt{11} )(5 - \sqrt{11} ) \\ putting \: formula \: (x - y) (x + y)= {x}^{2} - {y}^{2} \\ = {5}^{2} - { \sqrt{11} }^{2} \\ = 25 - 11 \\ = 14 (5 + \sqrt{11} )(5 - \sqrt{11} ) \\ putting \: formula \: (x - y) (x + y)= {x}^{2} - {y}^{2} \\ = {5}^{2} - { \sqrt{11} }^{2} \\ = 25 - 11 \\ = 14](https://tex.z-dn.net/?f=%285++%2B+++%5Csqrt%7B11%7D+%29%285+-++%5Csqrt%7B11%7D+%29+%5C%5C+putting+%5C%3A+formula+%5C%3A+%28x+-+y%29+%28x+%2B+y%29%3D++%7Bx%7D%5E%7B2%7D++-++%7By%7D%5E%7B2%7D++%5C%5C++%3D++%7B5%7D%5E%7B2%7D++-++%7B+%5Csqrt%7B11%7D+%7D%5E%7B2%7D++%5C%5C++%3D+25+-+11+%5C%5C++%3D+14)
Hope this helps u...
Hope this helps u...
muskanvirk:
very nice
Answered by
2
Heya !
••••• ••••• ••••• Answer ••••• ••••• •••••
( 5 + √11 ) ( 5 - √11 )
[solve using → ( a - b ) ( a + b ) = a raised to the power 2 - b raised to the power 2]
= 5 raised to the power 2 - √11 raised to the power 2 or(5^2 - √11^2)
=25 - 11
= 14
Its Simple !
Hope this helps
@PoojaBBSR
••••• ••••• ••••• Answer ••••• ••••• •••••
( 5 + √11 ) ( 5 - √11 )
[solve using → ( a - b ) ( a + b ) = a raised to the power 2 - b raised to the power 2]
= 5 raised to the power 2 - √11 raised to the power 2 or(5^2 - √11^2)
=25 - 11
= 14
Its Simple !
Hope this helps
@PoojaBBSR
Similar questions
Social Sciences,
8 months ago
Social Sciences,
8 months ago
Biology,
1 year ago
Science,
1 year ago
Math,
1 year ago
History,
1 year ago